1997
DOI: 10.1111/j.1398-9995.1997.tb00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum tryptase levels in adverse drug reactions

Abstract: We evaluated the usefulness of individual tryptase levels and variations after adverse drug reactions in 64 patients. Our aim was to find a tool for the diagnosis of drug allergy. Thirty-seven subjects were confirmed to have drug allergy, 12 had nonsteroidal anti-inflammatory drug (NSAID) reactions, five had negative controlled drug challenges (NAAR), and 10 had symptoms after placebo intake (PLA). Serum tryptase levels greatly increased after anaphylactic shocks (2242%) and anaphylaxis (710.5%). Patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Tryptase is not detectable in healthy individuals. Urticarial reactions can be associated with increased serum tryptase levels but may be lower than in anaphylaxis and may require multiple determinations after challenge with the suspected allergen [20]. Determination of tryptase in the serum is more convenient than histamine because it is chemically more stable and its biologic half-life is longer than that of histamine.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptase is not detectable in healthy individuals. Urticarial reactions can be associated with increased serum tryptase levels but may be lower than in anaphylaxis and may require multiple determinations after challenge with the suspected allergen [20]. Determination of tryptase in the serum is more convenient than histamine because it is chemically more stable and its biologic half-life is longer than that of histamine.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine concentrations reach peak levels within 5 minutes of the onset of symptoms and have a serum half-life of a few minutes (Ferrer et al, 2010), whereas PAF has a serum half-life ,15 minutes (Vadas et al, 2008). Several studies have shown that elevated levels of tryptase can be used as a biomarker of clinical hypersensitivity (Ordoqui et al, 1997;He et al, 2004;Payne and Kam, 2004;Fernandez et al, 2014b), and in accord with those studies, we found that mMCP-1 was elevated in sensitized mice from samples collected 2 hours after the asparaginase challenge (mMCP-1 is a mucosal mast cell granule-specific b-chymase that is released during basophil or mast cell degranulation in mice similar to tryptase in humans; Caughey, 2007). Furthermore, mMCP-1 concentrations were correlated with the severity of allergic reactions (Fig.…”
mentioning
confidence: 99%
“…Tryptase is a protease found in mast cells and is released on mast cell degranulation. A raised tryptase does not establish the presence of drug-specific IgE antibodies but is an indicator of mast cell mediator release [36]. Other tests, such as basophil histamine release, basophil degranulation, lymphocyte transformation, and macrophage migration inhibition, are helpful in a research setting but are not generally available.…”
Section: Tests For Ige Responsesmentioning
confidence: 96%